2014
DOI: 10.1155/2014/823029
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Tracking Algorithm for Distributed Encoding Fiber Bragg Grating Sensor Network

Abstract: Fiber Bragg Grating (FBG) sensor network has attracted more attention in online condition monitoring for the large mechanical equipment. By the efforts of the encoding scheme for sensor nodes, the capacity for the distributed FBG sensor network can be significantly improved. However, due to the increasing number of sensor nodes, the precision of tracking and locating for the FBG sensors has become a bottleneck that should be conquered. In order to realize more accurate and comprehensive condition monitoring fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…One paper by Zhang et al [ 293 ] brought attention to the increasing number of sensor nodes creating sensor networks ; the authors observed that the tracking and allocation of fiber Bragg sensors in electric sensing devices was becoming a bottleneck in condition monitoring; however, their research was not directly connected to rail transport.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…One paper by Zhang et al [ 293 ] brought attention to the increasing number of sensor nodes creating sensor networks ; the authors observed that the tracking and allocation of fiber Bragg sensors in electric sensing devices was becoming a bottleneck in condition monitoring; however, their research was not directly connected to rail transport.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%